Characteristics of liquid smoke from several kinds of waste. Issue 1 (September 2020) - Komarayati, S; Gusmailina,; Hendra, D; Winarni, I
Abstract: Research into making liquid smoke has been carried out using a 3 in 1 model furnace. The material used is waste consisting of wide leaf litter, a mixture of small leaf litter and mahogany bark. The results showed that the pH ranged from 3.82 to 4.69; specific gravity of 0.99. The content of phenol and acetic acid, liquid smoke, mahogany peel 0.34%, 0.62% and 0.86%, leaf litter mixture width 0.01% and 3.74% and small leaf litter mixture 0.06% and 0.88 %. From the results of the GCMS pyrolysis test, it was known that the acid derivatives, phenols and other components. The highest acid derived compound was obtained from liquid smoke of mixed litter of 66.53% relative and the lowest from liquid smoke of mixed leaf litter which was 8.78% relative. The highest phenol derivative content is from liquid smoke of mahogany bark of 29.45% relative and the lowest of liquid smoke of mixed litter is 4.92% relative. Liquid smoke obtained can be used as a trigger for plant growth and prevention of disease pests inplants.